2010
DOI: 10.1111/j.1748-0361.2010.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Community Pharmacy Counts and Closures Before and After the Implementation of Medicare Part D

Abstract: Unintended consequences of Medicare Part D may serve to reduce patient access to pharmacy services in opposition to the stated goals of the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…In fact, in numerous areas in the country, particularly in the Southwest and Plain states, independents dominate market share and are frequently the only pharmacy serving the local population. Ensuring pharmacies are available and accessible in these populations should be a public health priority considering independents are the most at-risk for pharmacy closures [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in numerous areas in the country, particularly in the Southwest and Plain states, independents dominate market share and are frequently the only pharmacy serving the local population. Ensuring pharmacies are available and accessible in these populations should be a public health priority considering independents are the most at-risk for pharmacy closures [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 With the availability of over 70,000 pharmacies in the United States, pharmacists are among the most accessible health care professionals who may prevent medication errors and provide counseling for pediatric patients with acute or chronic conditions and their parents or caregivers. 12 Despite having great potential to assume a role as a health and medication educator to children, studies have shown that these patients receive less attention from pharmacists because communications regarding medication use are often geared toward the children's parents or caregivers. 13 As medication experts, pharmacists play a vital role in counseling children in adhering to their medication regimens through direct collaboration and communication about safe and effective use of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…However, rural residents report several barriers to accessing healthcare including transportation difficulties and distance to care, social isolation, financial constraints, limited health care facilities (hospitals and pharmacies), physician shortages, and lack of access to specialist care [14-19]. Indeed, in the US, rural areas contain 19% of the population but only 11% of the physician workforce [15], and the ratio of specialists per population consistently declines as locations become smaller and more remote [15,17].…”
Section: Introductionmentioning
confidence: 99%